Caries inhibition with a CO2 9.3 μm laser: An in vitro study. Issue 5 (13th April 2016) - Rechmann, Peter; Rechmann, Beate M.T.; Groves, William H.; Le, Charles Q.; Rapozo‐Hilo, Marcia L.; Kinsel, Richard; Featherstone, John D.B.
Abstract : Background and Objectives: The caries preventive effects of different laser wavelengths have been studied in the laboratory as well as in pilot clinical trials. The objective of this in vitro study was to evaluate whether irradiation with a new 9.3 μm microsecond short‐pulsed CO2 ‐laser could enhance enamel caries resistance with and without additional fluoride applications. Study Design/Materials and Methods: One hundred and one human tooth enamel samples were divided into seven groups. Each group was treated with different laser parameters (CO2 ‐laser, wavelength 9.3 μm, 43 Hz pulse‐repetition rate, pulse duration between 3 µs at 1.5 mJ/pulse to 7 µs at 2.9 mJ/pulse). A laboratory pH‐cycling model followed by cross‐sectional microhardness testing determined the mean relative mineral loss delta Z (Δ Z ) for each group to assess caries inhibition in tooth enamel by the CO2 9.3 µm short‐pulsed laser irradiation. The pH‐cycling was performed with or without additional fluoride. Results: The non‐laser control groups with additional fluoride had a relative mineral loss (Δ Z, vol% × µm) that ranged between 646 ± 215 and 773 ± 223 (mean ± SD). The laser irradiated and fluoride treated samples had a mean Δ Z ranging between 209 ± 133 and 403 ± 245 for an average 55% ± 9% reduction in mineral loss (ANOVA test, P < 0.0001). Increased mean mineral loss (Δ Z between 1166 ± 571 and 1339 ± 347) was found for the non‐laser treated controls without additional fluoride. In contrast, the laser treated groups without additional fluoride showed a Δ Z between 470 ± 240 and 669 ± 209 (ANOVA test, P < 0.0001) representing an average 53% ± 11% reduction in mineral loss. Scanning electron microscopical assessment revealed that 3 µs pulses did not markedly change the enamel surface, while 7 µs pulses caused some enamel ablation. Conclusion: The CO2 9.3 µm short‐pulsed laser energy renders enamel caries resistant with and without additional fluoride use. The observed enhanced acid resistance occurred with the laser irradiation parameters used without obvious melting of the enamel surface as well as after irradiation with energies causing cutting of the enamel. Lasers Surg. Med. 48:546–554, 2016. Published 2016. This article is a U.S. Government work and is in the public domain in the USA